Particulate air pollution and mortality in Dublin 1980-1996 - Goodman, Patrick Gerard (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2000)
Air pollution in Dublin was studied for the period from 1980 to 1996. The factors which contribute to air pollution were investigated, and the nature of particulate air pollution is discussed. The trends in air pollution, and the Government interventions in relation to fuel usage, and air quality were evaluated. All non-accidental mortality for residents of Dublin County Borough was studied for the same period. The study covers 16.75 years, or 6119 days. A total of 80,307 deaths used in the study. Giving an average of 13.2 deaths per day.
Keywords: Respiratory Medicine, Ph.D.; Ph.D. Trinity College Dublin